Analisis Aspek Keamanan Informasi Data Pasien Pada Penerapan RME di Fasilitas Kesehatan - Siti Sofia; Efri Tri Ardianto; Niyalatul Muna; Sabran Sabran (Indonesian Journal Publisher, 2022)
Data security issues are becoming increasingly serious as the trend of data theft is increasing. This causes not only material losses but also psychological victims. The purpose of this study was to determine how the information security of patient data in the application of RME in terms of information security aspects. The method used is a literature review by analyzing 20 articles from various sources. The results of the study show that from the articles reviewed in terms of 6 security aspects, namely username and password, changes or deletions of data by administrators, electronic signatures and the use of PINs, aspects of using data backup processes to anticipate patient data hacking, restrictions on access rights by using user id & password for each user, as well as log file usage. Overall, health facilities basically have carried out data security on the information systems they use, but in practice there are still health facilities that do not fully meet the data security aspect or are not optimal in using the techniques used. System managers need to develop techniques or ways to secure data more optimally that can fulfill 6 aspects of information security in electronic medical records.